“PEACEFUL” EXPANSION OF THE RUSSIAN FEDERATION IN UKRAINE (1991 – 2014) - ZABOLOTNIUK, Volodymyr; KOTYLEVSKYI, Oleg (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the research is to study and elucidate the process of Russia’s territorial expansion in Ukraine in 1991 – 2014 and the role of the pro-Russian political and public agents of influence in it. The research methodology is based on the general scientific principles of historicism, objectivity and systematicity. There have been used general scientific methods: analysis, synthesis, periodization and the others, as well as special methods of historical research: historical genetic, historical systemic, historical comparative. The scientific novelty of the obtained results consists in the comprehensive analysis of the process of the so-called “peaceful” expansion of the Russian Federation in Ukraine in 1991 – 2014, without use of the armed force. Taking into consideration some separate examples, it has been proved that the war of the Russian Federation against Ukraine has historical roots from the beginning of its declaration of independence in 1991. The relations between Russia and Ukraine, as two sovereign states, during this period were not good-neighbourly, but were accompanied by constant territorial claims on the part of the Russian Federation, as open, and veiled, through the pro-Russian political parties, separatist movements, religious organizations, and other political and public agents of influence. Conclusions. The Russian aggression against Ukraine began in 1991 after its independence. The main goal of the Russian “peaceful” expansion was the destruction of sovereign and independent Ukraine or, in the event of its unreachability, keeping it under its control within a single “union” space. In order to achieve this goal, Russia imposed political, economic, religious, cultural, informational, military and other pressure with the wide use of technologies of subversion, blackmail, lies, intimidation, provocations, etc. Russia masked its own participation in destructive processes in Ukraine and carried out expansion through various pro-Russian political parties and organizations, representatives of criminal oligarchic groupes, separatist movements, the Ukrainian Orthodox Church (Moscow Patriarchate) and some of its ministers, pro-Russian media and other agents of influence, who operated under Russian special services management. In 1991 – 2014, during the Russian expansion in Ukraine, there were distinguished two conditional stages. The first stage, from August 26, 1991 to September 29, 2003, from the right of the Russian raising the issue on revising the state borders of the postsoviet republics, if they do not coexist within the unified space of the Union. It was considered to be the biggest crisis in the Russo-Ukrainian relations at the time, when Russia resorted to the use of force against Ukraine before the conflict had broken out regarding Kosa Tuzla Island. The second stage took place from September 29, 2003 to February 20, 2014, which began with the conflict around Kosa Tuzla Island, ended with the termination of the so-called “peaceful” expansion after the Revolution of Dignity in 2014, and then the beginning of the Ukrainian Crimea and Sevastopol occupation. There are several cites on the separate provisions of regulatory legal acts of Russia and Ukraine in the article, which strengthens the author’s argumentation and outcomes on a chosen topic. Key words: Russian Federation, Ukraine, hybrid warfare, Russo-Ukrainian war, expansion, territorial expansion, agents of influence, separatism, occupation of Crimea, self-proclaimed organizations “DPR” and “LPR”.